Fan C Co; Manufacturing Shoes / Norhafiza Yusoff ... [et al.] - Yusoff, Norhafiza; Alwi, Azura; Basir, Marlia; Saad, Amizan (2001)
FAN C Co' is a company that will be organize six month after graduation. Our company is produce shoes. We also a supplier for this shoes. Our product is suitable for young teenagers especially male. We also want to produce our product through Kedah, Perlis and Penang market. We have four partners in this company. They are Norhafiza Bt. Yusoff as a general manager and operational manager, Azura Bt. Alwi as a financial manager, Marlia Bt. Basir as a administration manager and Amizan B. Saad as a marketing manager. Every partner's assent for every post that have been given. Our factory or business will cost RM99, 910 for the business build. We hope that our company will get RM300,000 as a profit. It is because the profit will cover cost that we use before it. We also hope that our profit will increase month-by-month or year-by-year. If it happens, it will give back our cost that we have invest to build this business. Our location is Mergong Industrial Area in Alor Setar, Kedah. We choose this location because the location is so strategic and good potential to develop in the coming year.